2022
DOI: 10.1155/2022/1645089
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion System for the Elderly’s Daily Body Functions Based on Nanoprotective Technology

Abstract: With the acceleration of China’s aging trend, the physical health of the elderly needs more attention and research from us. In particular, many elderly people are prone to accidental injuries during exercise, so how to protect the health of the elderly through high-tech is worthy of more in-depth research. This measure can promote the establishment of a health system for the elderly. This article is mainly based on the research on the health promotion system of the elderly’s daily body functions based on nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Intelligent health promotion systems not only offer low-cost, safe, and reliable personalized health promotion services but also facilitate the exchange of critical information between numerous Internet of Things terminals and various health care service systems, thereby improving the efficiency and cost-effectiveness of health care services. Several studies have demonstrated the potential of intelligent health promotion systems in promoting population health and supporting health care [21][22][23][24]. For instance, Hu and Hao [23] found that a daily physical functioning and health promotion system based on nanoprotective technology effectively enhances the health of older adults and provides protection during exercise.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Intelligent health promotion systems not only offer low-cost, safe, and reliable personalized health promotion services but also facilitate the exchange of critical information between numerous Internet of Things terminals and various health care service systems, thereby improving the efficiency and cost-effectiveness of health care services. Several studies have demonstrated the potential of intelligent health promotion systems in promoting population health and supporting health care [21][22][23][24]. For instance, Hu and Hao [23] found that a daily physical functioning and health promotion system based on nanoprotective technology effectively enhances the health of older adults and provides protection during exercise.…”
Section: Significancementioning
confidence: 99%
“…Several studies have demonstrated the potential of intelligent health promotion systems in promoting population health and supporting health care [21][22][23][24]. For instance, Hu and Hao [23] found that a daily physical functioning and health promotion system based on nanoprotective technology effectively enhances the health of older adults and provides protection during exercise. Similarly, Sun et al [19] applied an intelligent, personalized, exercise prescription based on an eHealth promotion system to a community group of middle-aged and older people, resulting in significant improvements in some of the health outcomes of middle-aged and older community residents.…”
Section: Significancementioning
confidence: 99%